Management of Construction Waste in Nuclear and Thermal Power Plant Projects in India - Seethapathy, Sathiyamurthy; Henderson, Jane Helena (Penerbit Universiti Sains Malaysia, 2017)
Waste in construction is important both from the perspective of productivity and from environmental considerations. Mostly actual quantum of waste generation exceeds the percentage envisaged initially, causing needless utilization of both natural and human resources. It is understood from project and construction managers during site survey that there is plenty of scope for enhancing project productivity simply by minimizing waste out of construction and also saving the cost as well as extraction of natural resources. This paper attempts to identify the causes towards generation of waste of different types of building materials during various stages of construction in different power plant projects in India. Subsequent to identifcation, methods are proposed to mitigate the generation of construction wastes by adopting appropriate construction and management checks and methods, which allow waste reduction. The use of various building materials in different types of projects has different impact on the amount of waste generation, environment, and cost. Research data were gathered from the analysis of fve power plant projects under construction or already completed in different states in India. The causes of such occurrences of each item and details have been analysed from the questionnaire survey and the same was processed for normalizing, data cleaning, and reliability analysis done through SPSS. The result of the frst questionnaire was used along with site inputs/factual data to project the tabulation of perception versus reality. Furthermore, a second questionnaire was initiated for the validation of the above using non parametric statistic test and suitable recommendations were given to reduce wastage. The research paper reveals the major root causes for material wastage in construction of power plant projects and proper awareness to be created to the relevant project team by training. The fndings of this paper would help in enhancing project productivity during construction, cost savings to the extent of 1.667% to 1.941% of total project cost and minimizing the extraction of natural resources.